Contribution of Implicit/Explicit Self-Esteem and Gender in Psychopathic Traits at Adolescence - Habersaat, Stéphanie (Criminal justice and behavior, 2018)
The present study aimed to investigate gender-specific combinations of implicit and explicit self-esteem, helping to understand psychopathic traits (lifestyle, affective, and interpersonal) in adolescents at risk of delinquency. Two hundred thirty-one adolescent boys and girls (from public schools and child welfare and juvenile justice institutions) completed questionnaires measuring explicit self-esteem and psychopathic traits, as well as a computerized Implicit Association Test (IAT) assessing implicit self-esteem. Boys at risk of delinquent behaviors with anxious self-esteem (high implicit/low explicit) as well as at-risk girls with defensive self-esteem (low implicit/high explicit) displayed the highest scores in interpersonal and lifestyle traits. No relationship was found between gender-specific combinations of self-esteem and affective traits. Two gender-specific profiles were identified among the group at risk of delinquent behaviors: Girls with a defensive self-esteem (low implicit/high explicit) and boys with an anxious (or damaged) self-esteem (high implicit/low explicit) presented more interpersonal and lifestyle traits than other groups.